Exploratory and Collaborative Learning Scenarios in Virtual World using Unity-based Technology - Wilding, K.; Chang, Vanessa; Gütl, C. (2015)
This paper focuses on learning tools developed for the integration in virtual learning worlds that enable instructors to create in-world scenarios more easily. The tools were implemented in consideration of several learning concepts on exploratory, collaborative and challenge-based approaches. It elaborates on the design and development of a virtual world project on two platforms, namely Unity and Open Wonderland which is based on an Egyptian learning world. Users explore the world to find, explore and discard information. Through the process of identification and elimination a story is formed. Users can share information and collaborate with other users in- world and the tasks are supported by tools embedded in the virtual world, such as Textchat, Itemboard and Chatbot. The virtual world in Unity has addressed some of the issues raised in Open Wonderland such as the graphics enhancements, level of interactivities and lessons learned from the first prototype.